Characteristics of cement-stabilized macadam containing surface-treated recycled aggregates. Issue 9 (2nd September 2021) - You, Lingyun; Yue, Yufei; Yan, Kezhen; Zhou, Yubo
Abstract : The objectives of this study are to investigate the performance of recycled cement-stabilized macadam (i.e., open-graded cement-stabilized macadam containing recycled aggregates, RCSM) and to develop two surface treatment approaches for the enhancement of RCSMs. The unconfined compressive test, indirect tensile test, compressive resilience modulus test, and drying shrinkage test were applied to evaluate the performance of RCSMs. In order to investigate the frost resistance of RCSMs, five freeze–thaw cycles were used to simulate the frost conditions. Two surface treatment approaches were developed in this study, i.e. the cement-silica fume mixes (Type-A) and the sodium silicate solution (Type-B). The preliminary results suggest that the proposed enhancing agents display different effects on the unconfined compressive strength, indirect tensile strength, compressive resilience modulus, and frost resistance of RCSMs, while the enhancement effects of Type-A performed better than Type-B. However, due to the hydration reaction and evaporation of the cement-silica fume on the surface of recycled aggregate, the drying shrinkage strain of RCSM enhanced or treated by Type-A was significantly higher than that of the natural RCSM and the RCSM treated by Type-B. It shall be noted that the crack due to drying shrinkage is the main damage to the cement-stabilized macadam (CSM). Therefore, the proposed enhancement approaches could be considered in the application of RCSM in civil engineering, but the drying shrinkage properties of cement-silica fume mixes (Type-A) treated RCSM should be further improved.